"Bisexuality" and the Politics of Normal in African Ethnography - Epprecht, Marc (Anthropologica, 2022)
The purpose of this article is to explore the contemporary implications of the dismissal of "bisexuality" in the ethnography of sub-Saharan Africa. It problematizes the ways in which same-sex sexuality was represented in African ethnography, showing how colonial-era anthropologists tended to suppress, minimize or exoticize evidence of such practices in conformity with colonial ideologies, practices and prevailing debates around gender and sexuality in Europe and America. In the light of critiques launched by feminist, postcolonial and queer theorists against such anthropological representations, this paper demonstrates that the continual denial of "bisexuality" in Africa in the colonial era has become unsustainable